A pilot study of magnetic resonance fingerprinting in Parkinson's disease. (11th August 2020) - Keil, Vera Catharina; Bakoeva, Stilyana Peteva; Jurcoane, Alina; Doneva, Mariya; Amthor, Thomas; Koken, Peter; Mädler, Burkhard; Lüchters, Guido; Block, Wolfgang; Wüllner, Ullrich; Hattingen, Elke
Abstract : Parkinson's disease (PD) affects more than six million people, but reliable MRI biomarkers with which to diagnose patients have not been established. Magnetic resonance fingerprinting (MRF) is a recent quantitative technique that can provide relaxometric maps from a single sequence. The purpose of this study is to assess the potential of MRF to identify PD in patients and their disease severity, as well as to evaluate comfort during MRF. Twenty‐five PD patients and 25 matching controls underwent 3 T MRI, including an axial 2D spoiled gradient echo MRF sequence. T1 and T2 maps were generated by voxel‐wise matching the measured MRF signal to a precomputed dictionary. All participants also received standard inversion recovery T1 and multi‐echo T2 mapping. An ROI‐based analysis of relaxation times was performed. Differences between patients and controls as well as techniques were determined by logistic regression, Spearman correlation and t‐test. Patients were asked to estimate the subjective comfort of the MRF sequence. Both MRF‐based T1 and T2 mapping discriminated patients from controls: T1 relaxation times differed most in cortical grey matter (PD 1337 ± 38 vs. control 1386 ± 37 ms; mean ± SD; P = .0001) and, in combination with normal‐appearing white matter, enabled correct discrimination in 85.7% of cases (sensitivity 83.3%; specificity 88.0%; receiver‐operating characteristic [ROC]) area under the curve [AUC] 0.87), while for T2 mapping the left putamen was the strongest classifier (40.54 ± 6.28 vs. 34.17 ± 4.96 ms; P = .0001), enabling differentiation of groups in 84.0% of all cases (sensitivity 80.0%; specificity 88.0%; ROC AUC 0.87). Relaxation time differences were not associated with disease severity. Standard mapping techniques generated significantly different relaxation time values and identified other structures as different between groups other than MRF. Twenty‐three out of 25 PD patients preferred the MRF examination instead of a standard MRI. MRF‐based mapping can identify PD patients with good comfort but needs further assessment regarding disease severity identification and its potential for comparability with standard mapping technique results. Abstract : Magnetic resonance fingerprinting (MRF)‐based T1 and T2 mapping can help identify Parkinson's disease patients based on regional relaxation time, but differs from standard mapping results. Disease severity could not be associated with relaxation times. T1 relaxation times differed most in cortical grey matter rather than in the basal ganglia.